Comprehensive Midwifery Services As An Effort To Reduce Maternal Mortality Rates - Astin Nur Hanifah; Cakrawati Cakrawati; Rezqiqah Aulia Rahmat (International Journal of Health Sciences, 2026)
The Maternal Mortality Rate (MMR) remains an important indicator of public health status and the quality of maternal health services. One of the main strategies in reducing MMR is through comprehensive midwifery services that include antenatal, intranatal, postnatal, and family planning services. This study aims to determine the role of comprehensive midwifery services as an effort to reduce maternal mortality. This study uses a quantitative method with an analytical design and a cross-sectional approach. The study sample was mothers who received midwifery services at health service facility X. Data were collected using questionnaires and observation sheets, then analyzed using the Chi-Square test. The results of the study showed that good comprehensive midwifery services were significantly associated with a reduced risk of maternal complications that contributed to a decrease in MMR (p < 0.05). The conclusion of this study is that comprehensive midwifery services play an important role in efforts to reduce maternal mortality.